Calcium-Dependent and Synapsin-Dependent Pathways for the Presynaptic Actions of BDNF - Cheng, Qing; Song, Sang-Ho; Augustine, George J. (Frontiers in Cellular Neuroscience, 2017)
We used cultured hippocampal neurons to determine the signaling pathways mediating BDNF regulation of spontaneous glutamate and GABA release. BDNF treatment elevated calcium concentration in presynaptic terminals; this calcium signal reached a peak within 1 min and declined in the sustained presence of BDNF. This BDNF-induced transient rise in presynaptic calcium was reduced by SKF96365, indicating that BDNF causes presynaptic calcium influx via TRPC channels. BDNF treatment increased the frequency of miniature excitatory postsynaptic currents (mEPSCs). This response consisted of two components: a transient component that peaked within 1 min of initiating BDNF application and a second component that was sustained, at a lower mEPSC frequency, for the duration of BDNF application. The initial transient component was greatly reduced by removing external calcium or by SKF96365 treatment, as well as by Pyr3, a selective blocker of TRPC3 channels. In contrast, the sustained component was unaffected by these treatments but was eliminated by U0126, an inhibitor of the MAP kinase pathway, as well as by genetic deletion of synapsins in neurons from a synapsin triple knock-out (TKO) mouse. Thus, two pathways mediate the ability of BDNF to enhance spontaneous glutamate release: the transient component is arises from calcium influx through TRPC3 channels, while the sustained component is mediated by MAP kinase phosphorylation of synapsins. We also examined the ability of these two BDNF-dependent pathways to regulate spontaneous release of the inhibitory neurotransmitter, GABA. BDNF had no effect on the frequency of spontaneous miniature inhibitory postsynaptic currents (mIPSCs) in neurons from wild-type mice, but surprisingly did increase mIPSC frequency in synapsin TKO mice. This covert BDNF response was blocked by removal of external calcium or treatment with SKF96365 or Pyr3, indicating that it results from calcium influx mediated by TRPC3 channels. Thus, the BDNF-activated calcium signaling pathway can also enhance spontaneous GABA release, though this effect is suppressed by synapsins under normal physiological conditions.